New data on the distribution of Amaranthus retroflexus and Brassica juncea in Mongolia - V. I. Dorofeyev; Е. Ganbold (Труды по прикладной ботанике, генетике и селекции, 2020)
A study of the Mongolian flora and a survey of the herbarium collections of the Institute of General and Experimental Biology, Mongolian Academy of Sciences, conducted in 2019, provided new information on the geographical distribution of Amaranthus retroflexus (Amaranthaceae, Chenopodiaceae s.l.) and Brassica juncea (Cruciferae, Brassicaceae) in Mongolia.